Initial lessons from public-private partnerships in drug and vaccine development. - Wheeler, C. (World Health Organization, 2001)
In recent years, venture capital approaches have delivered impressive results in identifying and funding promising health discoveries and bringing them to market. This success has inspired public sector experiments with "social venture capital" approaches to address the dearth of affordable treatment and prevention for diseases of the developing world. Employing the same focus on well-defined and measurable objectives, and the same type of connections to pool and deploy resources as their for-profit counterparts, social venture capitalists seek to use the tools and incentives of capitalism to solve one of its biggest failures: the lack of drugs and vaccines for diseases endemic to low-income populations. As part of a larger trend of partnerships emerging in health product donation and distribution, public-private partnerships for pharmaceutical development have led research and development (R&D) efforts to generate more accessible and efficacious products for diseases such as malaria, tuberculosis, and AIDS. In this article, three R&D-focused partnerships are explored: the International AIDS Vaccine Initiative; the Medicines for Malaria Venture; and the newly formed Global Alliance for TB Drug Development. The article highlights key elements essential to the success of these ventures.